Cortactin as a potential predictor of second esophageal neoplasia in hypopharyngeal carcinoma. Issue 2 (April 2019) - Lien, Ching-Feng; Hwang, Tzer-Zen; Lin, Tsun-Mei; Liu, Kai-Wen; Lin, Bor-Shyh; Wang, Chih-Chun; Yang, Chuan-Chien; Yeh, Shyh-An
Abstract: Objective: Hypopharyngeal carcinoma has a very poor prognosis. The high incidence of second esophageal neoplasia is one of the major causes. To establish an efficient follow-up scheme for increasing the diagnostic yield and reducing the adverse impact of second esophageal neoplasia on survival, the purpose of this study was to explore a biomarker to predict second esophageal neoplasia. Methods: In this retrospective cohort study, consecutive tissue specimens from those patients who underwent tumor resection between September 2007 and October 2015 were collected. Gene amplification was performed by real-time PCR. The expression of cortactin was evaluated by immunohistochemistry. The predictive risk factors of developing second esophageal neoplasia and prognostic factors related to survival were analyzed. Results: A total of 187 patients were included with a mean follow-up of 48 months (12–118 months). Second esophageal tumors were found in 53 (28.3%), including 41 (21.9%) esophageal squamous cell carcinoma and 12 severe dysplasia. The results of multivariate analyses revealed that age (OR 2.81, 95% CI 1.16–6.78), cortactin overexpression (OR 2.49, 95% CI 1.17–5.33), and stage IV versus I (OR 6.49, 95% CI 1.68–25.18) were independent predictors of second esophageal neoplasia, and second esophageal neoplasia (HR 1.78, 95% CI 1.05–3.01) was an independent predictor of overall survival. Conclusion: This is the first report to identify a potential biomarker for predicting second esophageal neoplasia in patients with hypopharyngeal carcinoma. In those patients with cortactin overexpression and younger age (≤60 years old), close surveillance for second esophageal neoplasia is required. In addition, the real effect of cortactin overexpression on development of primary esophageal carcinoma is required to be validated in a large cohort study.